Нормативне забезпечення компетентності персоналу дослідних лабораторій - Сколоздра, Мирослава (Видавництво Національного університету «Львівська політехніка», 2009)
The human factor and his influence on quality of measuring process in testing laboratories was considering in the article. The analysis of existent normative base and methodology of accreditation of laboratories takking into account the ISO/IEC options was carried out.
Keywords: qualified personnel; research laboratory; cjmpetence; standart; system quality